Contemporary carbon accumulation in a boreal oligotrophic minerogenic mire - a significant sink after accounting for all C-fluxes - NILSSON, MATS; SAGERFORS, JÖRGEN; BUFFAM, ISHI; LAUDON, HJALMAR; ERIKSSON, TOBIAS; GRELLE, ACHIM; KLEMEDTSSON, LEIF; WESLIEN, PER; LINDROTH, ANDERS (Global change biology, 2008)
Based on theories of mire development and responses to a changing climate, the current role of mires as a net carbon sink has been questioned. A rigorous evaluation of the current net C‐exchange in mires requires measurements of all relevant fluxes. Estimates of annual total carbon budgets in mires are still very limited. Here, we present a full carbon budget over 2 years for a boreal minerogenic oligotrophic mire in northern Sweden (64°11′N, 19°33′E). Data on the following fluxes were collected: land–atmosphere CO2 exchange (continuous Eddy covariance measurements) and CH4 exchange (static chambers during the snow free period); TOC (total organic carbon) in precipitation; loss of TOC, dissolved inorganic carbon (DIC) and CH4 through stream water runoff (continuous discharge measurements and regular C‐concentration measurements). The mire constituted a net sink of 27±3.4 (±SD) g C m−2 yr−1 during 2004 and 20±3.4 g C m−2 yr−1 during 2005. This could be partitioned into an annual surface–atmosphere CO2 net uptake of 55±1.9 g C m−2 yr−1 during 2004 and 48±1.6 g C m−2 yr−1 during 2005. The annual NEE was further separated into a net uptake season, with an uptake of 92 g C m−2 yr−1 during 2004 and 86 g C m−2 yr−1 during 2005, and a net loss season with a loss of 37 g C m−2 yr−1 during 2004 and 38 g C m−2 yr−1 during 2005. Of the annual net CO2‐C uptake, 37% and 31% was lost through runoff (with runoff TOC>DIC≫CH4) and 16% and 29% through methane emission during 2004 and 2005, respectively. This mire is still a significant C‐sink, with carbon accumulation rates comparable to the long‐term Holocene C‐accumulation, and higher than the C‐accumulation during the late Holocene in the region.